Management of horizontal crown fracture caused by traumatic injury with endorestoration treatment - Nanik Zubaidah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Traumatic injuries of teeth are the main cause of emergency treatment in dental practice. The horizontal crown fracture more frequently observed usually occurs in maxillary anterior region and young male patients. The most common type of coronal fracture is in the middle third, followed by root and apical part. Purpose: The aim of this case report is to present the management of crown fracture of teeth with pulp exposure caused by dental trauma with endorestoration treatment in order to reconstruct the shape and the function of the teeth. Case: A 22 years old male with horizontal crown fracture of anterior teeth. The patient asked for aesthetic dental treatment both for its form and function. Case management: This horizontal crown fracture of anterior teeth with pulp exposure caused by dental trauma still could be reconstructed, mainly by endorestoration treatment. The endodontic treatment with post and core insertion in the root canal then would increase its retention. Later, the porcelain crown would aesthetically recover its original form and function, therefore, it would improve the patient’s confidence and teeth function. Conclusion: Endorestoration treatment on anterior teeth with harizontal crown fractures and pulp exposure is able to recover the normal function, aesthetic, and self-confidence.Latar belakang: Trauma pada gigi merupakan penyebab utama perawatan darurat dalam praktek dokter gigi. Fraktur mahkota horisontal pada umunya terjadi pada gigi anterior rahang atas dan terjadi pada penderita pria muda. Jenis yang paling sering dari fraktur mahkota adalah pada sepertiga tengah, daerah akar dan apical. Tujuan: Laporan kasus ini menjelaskan penatalaksanaan fraktur mahkota gigi dengan pulpa terbuka akibat trauma dengan perawatan endorestorasi untuk mengembalikan bentuk dan fungsi gigi. Kasus: Penderita pria umur 22 tahun dengan fraktur mahkota horizontal pada gigi anterior. Penderita tersebut menginginkan perawatan estetik untuk mengembalikan bentuk dan fungsi giginya. Tatalaksana kasus: Fraktur akar horisontal gigi anterior dengan pulpa terbuka oleh karena trauma gigi dapat direstorasi dengan perawatan endorestorasi. Perawatan endodontic dengan pasak dan inti dimasukkan ke dalam saluran akar dapat meningkatkan retensi. Kemudian mahkota porselen dapat mengembalikan bentuk dan fungsinya, karena itu dapat meningkatkan percaya diri pasien dan fungsi giginya. Kesimpulan: Perawatan endorestorasi pada gigi anterior dengan fraktur mahkota harizontal dan pulpa terbuka dapat mengembalikan fungsi estetik dan percaya diri pasien.